2018
DOI: 10.1021/acs.jpcb.8b02193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nucleotide State on the Protofilament Conformation of Tubulin Octamers

Abstract: At the molecular level, the dynamic instability (random growth and shrinkage) of the microtubule (MT) is driven by the nucleotide state (GTP vs GDP) in the β subunit of the tubulin dimers at the MT cap. Here, we use large-scale molecular dynamics (MD) simulations and normal-mode analysis (NMA) to characterize the effect of a single GTP cap layer on tubulin octamers composed of two neighboring protofilaments (PFs). We utilize recently reported high-resolution structures of dynamic MTs to simulate a GDP octamer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 80 publications
(188 reference statements)
4
10
0
Order By: Relevance
“…This finding is consistent with previous in vitro (50) and in vivo (51) experiments that reported highly variable tapered tips for microtubules by high resolution imaging and microtubule tip tracking. It is also in line with previous work that suggested there is a flexibility difference between the two nucleotide-states, with GTP being softer at its intraand inter-dimer interface (29,35,41), or a bending preference (24,33) with GTPprotofilaments growing less curved or nearly straight compared to the extensive outward peeling observed for GDP-protofilaments.…”
Section: Thermokinetic Modeling Identifies a Preferred Bending Angle supporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with previous in vitro (50) and in vivo (51) experiments that reported highly variable tapered tips for microtubules by high resolution imaging and microtubule tip tracking. It is also in line with previous work that suggested there is a flexibility difference between the two nucleotide-states, with GTP being softer at its intraand inter-dimer interface (29,35,41), or a bending preference (24,33) with GTPprotofilaments growing less curved or nearly straight compared to the extensive outward peeling observed for GDP-protofilaments.…”
Section: Thermokinetic Modeling Identifies a Preferred Bending Angle supporting
confidence: 92%
“…More generally, as stated by the authors (31), analysis of residue contact map and CG bond strength and length is not a measure of the actual binding strength of tubulin dimers; rather, an energy landscape of the lateral and longitudinal interaction of the dimers needs to be calculated. In addition, while a number of other MD studies have contributed toward an atomistic understanding of intradimer bending mechanics (29,30), to our knowledge, previous studies have not examined the free energy of interdimer bending as a function of its nucleotide besides equilibrium trajectory analysis (35,36,41). Finally, previous studies have not estimated the nucleotide dependence of the strength of the longitudinal bond, generally regarded as stronger than the lateral bond.…”
Section: Introductionmentioning
confidence: 98%
“…To identify stiffnesses, characterizing conformational changes at longer timescales, we used NMA as a complementary approach. The squared mode frequency, related to each normal mode, can be reckoned into mechanical properties, such as bending stiffness/torsional rigidity, corresponding to the motion along the given mode [3638]. As illustrated by Table 4, NMA confirmed that inter-dimer interface was much more flexible than the intra-dimer interfaces in the GTP-state, but that was not true for the inter-dimer interface of GDP-tubulin tetramer.…”
Section: Resultsmentioning
confidence: 99%
“…The eigenvalue of n -th normal mode, λ n , is related to its angular frequency, . The related vibrational frequency and mechanical stiffness for each normal mode of tubulin oligomers can be estimated applying the linear elastic beam theory [37,38]. In our analysis we assumed that tubulin oligomers behave as freely vibrating elastic filaments.…”
Section: Methodsmentioning
confidence: 99%
“…Similar angular distributions were observed in the computational work by Grafmuller and Voth (2011) where they investigated GDP-and GTP-bound tubulin dimers and protofilaments. Manandhar et al (2018) simulated GDP octamers both with and without a single GTP cap layer using free energy calculations and also obtained similar distributions for intra-dimer bending angles. Such small values of bending angles imply that the microtubule is more rigid than a protofilament.…”
Section: Bending Of Protofilament and Microtubulementioning
confidence: 71%